Phytosynthesis of intracellular and extracellular gold nanoparticles by living peanut plant (Arachis hypogaea L.) - Raju, Dugyala; Mehta, Urmil J.; Ahmad, Absar (Biotechnology and Applied Biochemistry, 2012)
Inorganic nanomaterials of different chemical compositions are conventionally synthesized under harsh environments such as extremes of temperature, pressure, and pH. Moreover, these methods are eco-unfriendly and cumbersome, yield bigger particles, and agglomerate because of not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions, namely room temperature, atmospheric pressure, and physiological pH. These methods are reliable, eco-friendly, and cheap. In this paper, we report for the first time the extracellular and intracellular synthesis of gold nanoparticles (GNPs) using living peanut seedlings. The formed GNPs were highly stable in solution and inside the plant tissue. Transmission electron microscopy revealed that extracellular GNPs distributions were in the form of monodispersed nanoparticles. The nanoparticles ranged from 4 to 6 nm in size. The intercellular nanoparticles were of oval shape and size ranged from 5 to 50 nm. Both extracellular and intracellular nanoparticles were further characterized by standard techniques. The formed GNPs inside the plant tissue were estimated by inductively coupled plasma spectrometry. This opens up an exciting possibility of a plant-based nanoparticle synthesis strategy, wherein the nanoparticles may be entrapped in the biomass in the form of a film or produced in the solution, both of which have interesting applications.
Keywords: cells; extracellular; living plant; Peanut; root; TEM

Gold nanoconjugates reinforce the potency of conjugated cisplatin and doxorubicin - Iram, S. (Colloids and Surfaces B: Biointerfaces, 2017)
Osteosarcoma or osteogenic sarcoma is the most common and prevalent cancerous tumor of bone and occurs especially in children and teens. Recent treatment strategy includes a combination of both chemotherapy and surgeries. Although, the use of single drug-based chemotherapy treatment remains unsatisfactory. Therefore, combinatorial therapy has emerged as a potential strategy for treatment with limited side- effects. Here, we evaluated the combinatorial anticancerous effect of cisplatin (CIS) and doxorubicin (DOX) bioconjugated bromelain encapsulated gold nanoparticles (B-AuNPs conjugated CIS and DOX) in the treatment of osteosarcoma. The synthesized B-AuNPs conjugated CIS and DOX were characterized by various characterization techniques like UV–vis spectroscopy, TEM, DLS and zeta potential to ensure the synthesis, size, shape, size distribution and stability. Drug loading efficiency bioconjugation of CIS and DOX was ensured by UV–vis spectroscopy. Bioconjugation of CIS and DOX was further confirmed using UV–vis spectroscopy, TEM, DLS, Zeta potential and FT-IR analysis. The combinatorial effect of CIS and DOX in B-AuNPs conjugated CIS and DOX showed highly improved potency against MG-63 and Saos-2 cells at a very low concentration where primary osteoblasts didn't show any cytotoxic effect. The apoptotic effect of B-AuNPs conjugated CIS and DOX on osteosarcoma and primary osteoblasts cells were analyzed by increased permeability of the cell membrane, condensed chromatin and deep blue fluorescent condensed nucleus. The results clearly showed that B-AuNPs conjugated CIS and DOX significantly improved the potency of both the chemotherapeutic drugs by delivering them specifically into the nucleus of cancer cells through caveolae-dependent endocytosis. Thus, the greater inhibitory effect of combinatorial drugs (B-AuNPs conjugated CIS and DOX) over single drug based chemotherapy would be of great advantage during osteosarcoma treatment.
Keywords: cells; chemotherapy; Cytology; Cytotoxicity; Drug interactions; dynamic light scattering; Gold; Molecular Biology; Platinum Compounds